2012
DOI: 10.1287/orsc.1110.0681
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Innovation: Supporting Valuable Unpredictability in the Creative Process

Abstract: Historical accounts of human achievement suggest that accidents can play an important role in innovation. In this paper, we seek to contribute to an understanding of how digital systems might support valuable unpredictability in innovation processes by examining how innovators who obtain value from accidents integrate unpredictability into their work. We describe an inductive, grounded theory project, based on 20 case studies, that looks into the conditions under which people who make things keep their work op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 37 publications
1
82
0
2
Order By: Relevance
“…It seems reasonable that we need approaches that on one hand can reduce destructive fragmentation, and on the other hand enhance valuable ditto to reach emergent design outcomes (see e.g. Austin et al, 2012). The latter is important to reflect on, given a future where ISD and innovation is widening into emergent design domains and emergent design solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems reasonable that we need approaches that on one hand can reduce destructive fragmentation, and on the other hand enhance valuable ditto to reach emergent design outcomes (see e.g. Austin et al, 2012). The latter is important to reflect on, given a future where ISD and innovation is widening into emergent design domains and emergent design solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the ambiguity of IDS and innovation has been recognized to be of value. In a study on digital innovation projects, Austin et al (2012) found that accidents such as breakage, malfunction, movement outside of intention, and accepted chain of logic can be of value to achieve novel design outcomes.…”
Section: Background On Isd and Innovationmentioning
confidence: 99%
“…may be seen as serving similar functions, namely being emotive markers of a felt understanding that only later is explicated. It is not relevant to address the controversy over Jobs' discourse and behavior (see Austin, 2012 for a balanced account) to realize that these exclamations were markers of small epiphanies in creative interactions. Both convey felt understandings whose sharing and reception may trigger explication processes and further bouts of idea development.…”
Section: Follow a History Of Preparation And Persistencementioning
confidence: 99%
“…In some contexts, what counts as getting things right is quite clearly defined and well understood, while in others, the process may lead to unexpected breakthroughs outside the scope of the original project. Here are four examples of what has been labeled accidental innovation (Austin, Devin, & Sullivan, 2012):…”
Section: Innovation and Failurementioning
confidence: 99%